FOOD AS MEDICINE: MANAGING NON-COMMUNICABLE DISEASES IN HIV-POSITIVE INDIVIDUALS THROUGH DIET AT BUSIA COUNTY HOSPITAL - Wekesa , Brian Odhiambo (Ayden Journal of Agriculture and Allied Studies, 2025)
Non-communicable diseases (NCDs) account for 41 million deaths annually, representing 74% of all global fatalities, with a disproportionate burden on low- and middle-income countries. Of these deaths, 17 million are premature, occurring before the age of 70, with 86% of these individuals living in low-resource settings. Among these, People Living with HIV (PLHIV) are at heightened risk of developing chronic NCDs, exacerbating the already significant health challenges they face. As the profiles of PLHIV and their use of antiretroviral therapy (ART) evolve, the implications for both clinical care and management in urban and rural settings become increasingly important. The role of nutrition in the lives of PLHIV cannot be overstated, as poor dietary habits accelerate disease progression, elevate morbidity, and decrease life expectancy. Proper nutrition is recognized as a critical element for improving the quality of life (QoL) for those living with HIV, supporting immune function, and enhancing treatment outcomes. This study seeks to explore the intersection between diet and NCD management among PLHIV, emphasizing the need for tailored nutritional interventions that can significantly improve health outcomes, particularly in resource-limited settings